Developmental Plasticity and Robustness of a Nematode Mouth-Form Polyphenism - Sieriebriennikov, Bogdan; Sommer, Ralf J. (Frontiers in Genetics, 2018)
In the last decade, case studies in plants and animals provided increasing insight into the molecular mechanisms of developmental plasticity. When complemented with evolutionary and ecological analyses, these studies suggest that plasticity represents a mechanism facilitating adaptive change, increasing diversity and fostering the evolution of novelty. Here, we summarize genetic, molecular and evolutionary studies on developmental plasticity of feeding structures in nematodes, focusing on the model organism Pristionchus pacificus and its relatives. Like its famous cousin Caenorhabditis elegans, P. pacificus reproduces as a self-fertilizing hermaphrodite and can be cultured in the laboratory on Escherichia coli indefinitely with a four-day generation time. However, in contrast to C. elegans, Pristionchus worms show more complex feeding structures in adaptation to their life history. Pristionchus nematodes live in the soil and are reliably found in association with scarab beetles, but only reproduce after the insects’ death. Insect carcasses usually exist only for a short time period and their turnover is partially unpredictable. Strikingly, Pristionchus worms can have two alternative mouth-forms; animals are either stenostomatous (St) with a single tooth resulting in strict bacterial feeding, or alternatively, they are eurystomatous (Eu) with two teeth allowing facultative predation. Laboratory-based studies revealed a regulatory network that controls the irreversible decision of individual worms to adopt the St or Eu form. These studies revealed that a developmental switch controls the mouth-form decision, confirming long-standing theory about the role of switch genes in developmental plasticity. Here, we describe the current understanding of P. pacificus mouth-form regulation. In contrast to plasticity, robustness describes the property of organisms to produce unchanged phenotypes despite environmental perturbations. While largely opposite in principle, the relationship between developmental plasticity and robustness has only rarely been tested in particular study systems. Based on a study of the Hsp90 chaperones in nematodes, we suggest that robustness and plasticity are indeed complementary concepts. Genetic switch networks regulating plasticity require robustness to produce reproducible responses to the multitude of environmental inputs and the phenotypic output requires robustness because the range of possible phenotypic outcomes is constrained. Thus, plasticity and robustness are actually not mutually exclusive, but rather complementary concepts.